2013
DOI: 10.1016/j.enpol.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact assessment of Turkey's post-Kyoto vision on emission trading

Abstract: For the post-Kyoto period, Turkey strongly emphasizes the establishment of national emission trading system by 2015 and its integration with the EU ETS along its accession process to the EU. In this paper, we study the mechanisms of adjustment and economic welfare consequences of various ETS regimes that Turkey considers to apply by 2020, i.e. regional ETS and international trading within the EU ETS. We conduct our analysis under the current EU 20-20-20 emission target, 20%, and also under its revised version,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They proposed a policy reducing existing tax rates and applying carbon and energy taxes. In another study, Akin-Olcum and Yeldan [42] analyzed several emissions trading system (ETS) regimes for Turkey under the EU 20-20-20 emissions target and its revised version, 30%. The authors built a multi-regional, multi-sectoral applied general equilibrium model, and found that Turkey would have economic gains from linking with the EU ETS under the 20% cap, but it would suffer critical output loss under the 30% cutback.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They proposed a policy reducing existing tax rates and applying carbon and energy taxes. In another study, Akin-Olcum and Yeldan [42] analyzed several emissions trading system (ETS) regimes for Turkey under the EU 20-20-20 emissions target and its revised version, 30%. The authors built a multi-regional, multi-sectoral applied general equilibrium model, and found that Turkey would have economic gains from linking with the EU ETS under the 20% cap, but it would suffer critical output loss under the 30% cutback.…”
Section: Literature Reviewmentioning
confidence: 99%